2016
DOI: 10.1049/hve.2016.0063
|View full text |Cite
|
Sign up to set email alerts
|

Energy storage and harvesting in BaTiO 3 /epoxy nanodielectrics

Abstract: Composite nanodielectrics consisted of an epoxy resin and barium titanate nanoparticles were developed and characterised. Electrical measurements were performed via broadband dielectric spectroscopy. Dielectric results reveal the presence of three relaxation processes, which are attributed to (a) glass to rubber transition of the polymer matrix (α-mode), (b) rearrangement of polar side groups (β-mode) and (c) interfacial polarisation between system's constituents. The ability of the examined nanodielectrics to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The annular interconnected BT architecture has tilted the electric field distribution from the FEA investigations, which leads to high breakdown strength in the composite compared with those filled with vertically aligned BT fillers. High electric displacement (3.2 μC cm −2 at 100 kV cm −1 , 13.2 μC cm −2 at 400 kV cm −1 ) and resultant high-energy density (105 × 10 −3 J cm −3 at 100 kV cm −1 , 1812 × 10 −3 J cm −3 at 400 kV cm −1 ) and high efficiencies are achived in the epoxy/BT sponge composites, which are significantly enhanced compared with polymer/ceramic composites made from traditional strategies 16,45,[50][51][52] . Simulation as well as SKPM results show that enhancements of electric displacements and energy densities are mainly owing to the high local electric displacement.…”
Section: Resultsmentioning
confidence: 99%
“…The annular interconnected BT architecture has tilted the electric field distribution from the FEA investigations, which leads to high breakdown strength in the composite compared with those filled with vertically aligned BT fillers. High electric displacement (3.2 μC cm −2 at 100 kV cm −1 , 13.2 μC cm −2 at 400 kV cm −1 ) and resultant high-energy density (105 × 10 −3 J cm −3 at 100 kV cm −1 , 1812 × 10 −3 J cm −3 at 400 kV cm −1 ) and high efficiencies are achived in the epoxy/BT sponge composites, which are significantly enhanced compared with polymer/ceramic composites made from traditional strategies 16,45,[50][51][52] . Simulation as well as SKPM results show that enhancements of electric displacements and energy densities are mainly owing to the high local electric displacement.…”
Section: Resultsmentioning
confidence: 99%
“…τ (E, T ) = τ 0 e Q(E) kT (1) and Q(E) = Q 0 − αE (2) where, Q(E) Being the activation energy at electrical destruction. τ 0 ≈ (10 −12 − 10 −14 ) s is the atomic vibration period in solids, k is the Boltzmann constant, Q 0 is the value of the initial barrier of electrical destruction, E is the electric field intensity and α is a coefficient which depends on the local increase in the electrical field intensity and intermolecular cavities.…”
Section: B Thermal Property and Lifespansmentioning
confidence: 99%
“…In recent years, the application of polymer as dielectric materials in power grid has effectively improved the performance of power equipment, such as energy storage characteristics [1], [2], mechanical properties [3], electrical strength [4], [5] and so on. Many studies have shown that, on the basis of ensuring the original properties of the above polymeric dielectric materials, nano-fillers can further improve the properties of the materials through effective combination with the polymer matrix [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of a coefficient of energy efficiency considered to be necessary for the evaluation of the energy performance of the systems. The coefficient of energy efficiency (n eff ) is defined as the ratio of the retrieved energy upon the stored one with parameters, the voltage, the temperature and the time [13] (Equation (4)):…”
Section: Energy Storage and Harvesting/coefficientmentioning
confidence: 99%